Local People Knowledge about Plant Trees Species Inside Tropical Forest of Tengger Ranupani - Setyo Ayu Hardyanti; Luchman Hakim (Biotropika: Journal of Tropical Biology, 2014)
Degradation of  tropical forests in Indonesia is  known more widespread. The development of  societyactivities  is  known to be very fast, thus  it  causes  land degradation. An  effort  to make ecosystem reparation of the tropical forest through restoration becomes very important to be done. The success of these efforts cannot be separated from the local community factors. The purpose of this study  is  to determine rainforest woody plant species that are recognized, and utilized  also knowing the  public perceptions in tropical forest restoration. The method used is quantitative ethnobotany with estimatingthe significance of the plant based on the level of popularity  herbs known and frequently used by the society.  The data  were analyzed using the Relative Frequency of Citations (RFC) and Relative Importance (RI). There are thirtyfive plants that are mentioned by society. Eighteen species are woody plants. The highest value of RFC from the interview are pine (Casuarina junghuhniana) that the value is  1. It  is often  used to  fill the need  as a building material and firewood.  The  smallest value of  RFC is 0.07  randu bacin  (Pittosporum moluccanum).  It  is  caused of lacking knowledge of  the type  and the benefits of the plants. RI value or numbers of plants  that are most frequently mentioned is fir that is at 3.56.  Meanwhile,  the  smallest  value of  RI  is  randu bacin  (Pittosporum moluccanum)  of 0.31.  The society’s perception of woody plants is  quite well. The society  knows the benefits of forest plants and the  forest condition today.  The society’s  traditional knowledge in  benefitting  the  plants  is  to be hereditary. So that  society  makes  serious efforts  to  help  the activity of  forest restoration by planting vegetation. Keywords: degradation, forest, restoration, trees, utilization